SeaFilm Research Product bags ITEX Special Awards 2020 - Nor Salwana, Mohammad Idris (2020)
PEKAN, 21 November 2020 – SeaFilm Research Product (SF): Active Food Packaging Film produced by a lecturer from College of Engineering, Universiti Malaysia Pahang (UMP), Dr. Nurul Aini Mohd Azman bagged the Best Green Invention Award in the International Invention, Innovation & Technology Exhibition 2020 (ITEX 2020) which was conducted online for the first time this year.